FTIR-based measurements of self-broadening and self-shift coefficients as well as line strength in the first overtone band of HCl at 1.76 µM. (November 2015) - Li, Gang; Serdyukov, Anton; Gisi, Michael; Werhahn, Olav; Ebert, Volker
Abstract: FTIR spectra of the 2-0 band of HCl have been measured in the 5300–5900 cm −1 spectral region at 15 different pressures (0.05–2.5 bar) and at a spectral resolution of 0.07 cm −1 . For the first time, reliable and consistent self-induced broadening and shift coefficients for the complete HCl 2-0 band have been reported. Line intensities determined from a robust regression analysis with improved uncertainties are also presented. Compared to previous laser-based measurement for the R3 line {Ortwein et al., Appl Phys B: Lasers Opt 2010;100:341–7}, our newly measured γ s e l f coefficient and line intensity are 1.35% and 0.10% larger, respectively. Hartmann and Boulet {Hartmann & Boulet, JCP 113, 9000 (2000)} developed a formalism describing the relation between the shift coefficients of different vibrational bands and successfully applied to Ar–HF system. Our newly measured self-induced shift coefficients suggest that the H–B formalism is not suitable for describing the HCl–HCl collisional system. Highlights: 1st collisional self-broadening measurements of the entire HCl 2-0 band. 1st measurements of self-shift coefficients of the entire HCl 2-0 band. Measurements of HCl 2-0 line intensities with improved accuracy. Line intensities are in excellent agreement with HITRAN2012. Line intensities agree very well with most recent semi-empirical computations.